2010
DOI: 10.1002/hon.939
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation after chemotherapy for Hodgkin lymphoma

Abstract: Treatment for Hodgkin lymphoma can negatively affect fertility. This review summarizes data on fertility after chemotherapy in adult patients. Alkylating chemotherapy, especially if containing procarbazine and/or cyclophosphamide, is most harmful to gonadal functioning. Alkylating regimens cause prolonged azoospermia in 90-100% of men and ovarian failure in 5-25% of women under the age of 30. Non-alkylating chemotherapy, like ABVD, is much less harmful: one-third of male patients develop transient azoospermia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 115 publications
(75 reference statements)
0
46
0
10
Order By: Relevance
“…Both platinums (such as CBP) and anthracyclins (DOX) interfere with DNA replication and as such are particularly toxic to dividing granulosa cells of secondary and antral follicles, albeit with distinct toxicity profiles (55), and thus represent ideal targets for an MIS oncofertility intervention. CPA is an alkylating agent, a class that is particularly damaging to germ cells, and is the most problematic gonadotoxic chemotherapeutic in the clinic, particularly because it is often used in young girls with hematological cancers (57). We found that MIS had a particularly dramatic protective effect in the case of DNA-damaging agents (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Both platinums (such as CBP) and anthracyclins (DOX) interfere with DNA replication and as such are particularly toxic to dividing granulosa cells of secondary and antral follicles, albeit with distinct toxicity profiles (55), and thus represent ideal targets for an MIS oncofertility intervention. CPA is an alkylating agent, a class that is particularly damaging to germ cells, and is the most problematic gonadotoxic chemotherapeutic in the clinic, particularly because it is often used in young girls with hematological cancers (57). We found that MIS had a particularly dramatic protective effect in the case of DNA-damaging agents (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…40 The guidelines recommend fertility preservation (semen cryopreservation in male patients, ovarian tissue or oocyte cryopreservation in female patients) before the initiation of chemotherapy with alkylating agents or pelvic RT. 41,42 Oophoropexy should be considered to preserve ovarian function in premenopausal women if pelvic RT is contemplated.…”
Section: Treatment Guidelines Diagnosis and Workupmentioning
confidence: 99%
“…96,97 Other combinations (eg, ABVD) are only rarely associated with infertility. 42,98 Because women who have received chemotherapy with alkylating agents and who maintain short-term fertility may experience premature menopause, 40 this should be taken into consideration with respect to family planning.…”
Section: Myelosuppressionmentioning
confidence: 99%
“…At higher cumulative doses, alkylator containing regimens may cause prolonged azoospermia in 90-100 % of men. 55 A few studies have evaluated male fertility following cyclophosphamide-containing regimens given to children and young adults with sarcomas and other cancers [56][57][58] and suggest that the incidence of sterility will be low if the cyclophosphamide dose is less than 7.5 g/m 2 . Data concerning ovarian function following CT for female children and young adults with HL suggest that the ovaries of children and adolescents are less sensitive to the effects of alkylating agents than the ovaries of older women; females over 30 years have a much higher risk of acute ovarian failure.…”
Section: Gonadal Toxicitymentioning
confidence: 99%
“…However, with long-term follow-up, the cumulative risk of menopause before the age of 40 becomes the same irrespective of treatment age, and the incidence of early menopause in young female survivors may be as high as 37 %. 55,59,60 Options for fertility preservation in women receiving cytotoxic therapies are available in some jurisdictions (see, for example, recommendations from the network FertiPROTEKT [available at: www.fertiprotect.eu]).…”
Section: Gonadal Toxicitymentioning
confidence: 99%